APPLICATION OF BUSINESS CONTINUITY PROVISIONS IN BANKRUPTCY TO INCREASE THE VALUE OF BANKRUPTCY ASSETS - Siburian, Hendra Harianto S.; Nainggolan, Bernard; Harjono, Dhaniswara K. (JILPR Journal Indonesia Law and Policy Review, 2024)
APPLICATION OF BUSINESS CONTINUITY PROVISIONS (GOING CONCERN) IN BANKRUPTCY TO INCREASE THE VALUE OF BANKRUPTCY ASSETS (Decision No. 54/Pdt.Sus-PKPU/2020/PN Niaga Sby), the aim of this research is to determine the duties and authority of the curator in the management and/or or settlement of bankruptcy assets and to find out the application of the going concern provisions in the bankruptcy of PT. Banjar Intan Mandiri based on Decision No. 54/Pdt.Sus-PKPU/2020/PN Niaga Sby. The research method used in this study is a normative juridical research method with Law no. 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations. The results of this research are that the Curator has the authority to carry out the task of managing and/or settling all of the debtor's assets which become bankruptcy assets. This is because by law the Debtor loses his right to control and manage his assets which are included in the bankruptcy assets from the date the bankruptcy decision is declared. In carrying out its duties, the Curator is not required to obtain approval from or provide prior notification to the Debtor or any of the Debtor's organs, although in circumstances other than bankruptcy such approval or notification is required. The curator is obliged to take actions that can increase the value of the bankrupt assets. The application of business continuity provisions in bankruptcy cases is within the framework of legal protection for debtors and has a positive impact on increasing the company's economic value which in turn is used to pay debts to its creditors.